Dovetail double fixed ceramic lining plate and preparation process thereof

CN122916629APending Publication Date: 2026-10-16HEBEI LONGJIA METALLURGY EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611282647.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

中国专利CN222865585U公开了一种窑炉用陶瓷耐磨板,通过燕尾槽与燕尾块的插接结构实现衬板装配固定,但其固定方式以纯机械嵌合为主,粘接界面未做针对性改性处理,无法形成机械咬合与化学粘接的协同强化效果,抗冲击脱落性能仍有不足

Benefits of technology

1、本发明通过燕尾槽机械咬合与改性胶粘剂化学粘接相结合的双重固定方式,显著提高了陶瓷衬板与设备内壁的结合强度,有效避免了陶瓷衬板在强冲击、高磨损工况下的脱落问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916629A_ABST
    Figure CN122916629A_ABST
Patent Text Reader

Abstract

The application discloses a dovetail groove double-fixed ceramic lining plate and a preparation process, and belongs to the technical field of wear-resistant ceramic lining plates. The ceramic lining plate with a dovetail groove structure is prepared through the steps of batching, forming and high-temperature sintering; the functional groups of epoxy resin and a silane coupling agent are modified in sequence, and the ceramic lining plate is subjected to surface activation treatment by using a plasma technology. The dovetail groove mechanical occlusion and the modified adhesive chemical bonding are combined to form a double-fixed structure, the overall bonding strength is high, the product is wear-resistant and has outstanding impact resistance. The whole process is simple and stable in stability, can be adapted to various harsh industrial working conditions, and is suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of wear-resistant ceramic liner plates, specifically relating to a dovetail groove double-fixed ceramic liner plate and its preparation process. Background Technology

[0002] In heavy industries such as mining, cement, power, metallurgy, and coal, the inner walls of various conveying, crushing, and grinding equipment are subjected to high-speed impact and wear from materials for extended periods, resulting in short equipment lifespans, high maintenance costs, and severely impacting production efficiency. Wear-resistant ceramic liners, due to their superior properties such as high hardness, high wear resistance, and corrosion resistance, are widely used for the inner wall protection of these equipment, significantly extending their service life and reducing maintenance costs. With the continuous development of industrial technology, industrial production places increasingly higher demands on the performance of wear-resistant ceramic liners. They are required not only to possess excellent wear resistance and impact resistance, but also to be securely installed, resistant to detachment, and able to withstand harsh working conditions such as high temperature, high humidity, and strong impact.

[0003] Currently, the most common methods for fixing ceramic liners on the market are adhesive bonding, bolt fixing, and welding. Adhesive bonding involves directly attaching the ceramic liner to the inner wall of the equipment with adhesive, which is convenient and quick to install and does not damage the integrity of the ceramic liner. However, the adhesive is prone to aging and failure in environments with high temperature, high humidity, and oil, and the ceramic liner is prone to falling off under strong impact. Bolt fixing uses bolts to fix the ceramic liner to the inner wall of the equipment, which is relatively secure. However, the bolt holes can damage the overall structure of the ceramic liner, reducing its wear resistance and impact resistance. Moreover, the bolts themselves are also prone to wear from materials and need to be replaced regularly, increasing maintenance costs. Welding fixes the ceramic liner to the inner wall of the equipment using metal welding parts, which provides high fixation. However, the high temperature generated during welding can cause thermal stress in the ceramic liner, making it prone to cracking. In addition, welding is difficult, has a long construction period, and is costly. Furthermore, although some existing technologies employ dovetail groove mechanical fixing methods, most are purely mechanical fixation or use ordinary unmodified adhesives without targeted functional group modification of the adhesives or plasma surface pretreatment technology, resulting in insufficient interfacial bonding strength. For example, Chinese patent CN214698634U discloses a high-temperature and wear-resistant ceramic insert, which uses an assembly structure of ceramic parts and steel-based dovetail grooves, supplemented by central adhesive filling and welding reinforcement. However, it only uses a general-purpose adhesive and does not perform epoxy resin functional group modification and silane coupling agent interface optimization for the surface characteristics of alumina ceramics, nor does it perform activation pretreatment on the ceramic bonding surface. The interfacial bonding strength between the ceramic and the adhesive layer is limited, and under long-term strong impact and high wear conditions, interfacial peeling and liner loosening are prone to occur. Chinese patent CN222865585U discloses a ceramic wear-resistant plate for kilns, which uses a dovetail groove and dovetail block interlocking structure to assemble and fix the liner. However, its fixing method is mainly based on pure mechanical interlocking, and the bonding interface has not been specifically modified, so it cannot form a synergistic strengthening effect of mechanical interlocking and chemical bonding, and its impact resistance is still insufficient. At the same time, existing research on the modification of epoxy resin adhesives focuses on the toughening optimization of pure resin systems. For example, some studies have improved the elongation at break and bonding strength of the adhesive layer by polyurethane grafting modification of epoxy resin. However, such modification schemes are mainly designed for metal-to-metal and concrete bonding scenarios, and have not formed a systematic interface strengthening scheme by combining it with ceramic surface plasma activation and silane coupling agents. When applied to the fixing scenario of dovetail groove alumina ceramic liners, the interface bonding strength and environmental aging resistance are still difficult to meet the long-term use requirements of harsh working conditions.

[0004] This invention addresses the aforementioned deficiencies in existing technologies by providing a dovetail groove double-fixed ceramic liner and its manufacturing process. By designing a dovetail groove structure on the back of the ceramic liner, specifically modifying the epoxy resin adhesive and silane coupling agent, and employing plasma surface pretreatment technology, this invention achieves a dual-fixation effect combining mechanical and chemical bonding. This significantly improves the fixing firmness of the ceramic liner, enhances its wear resistance and impact resistance, and effectively solves the problem of existing ceramic liners easily detaching and cracking under harsh working conditions. Summary of the Invention

[0005] The purpose of this invention is to provide a dovetail groove double-fixed ceramic liner and its preparation process, which is achieved through the following steps: S1. Forming of the dovetail groove structure for ceramic liner: Alumina ceramic powder, silica powder, and magnesium oxide powder are mixed uniformly according to a mass ratio. Deionized water, sodium polyacrylate dispersant, and 0.8%-1.5% (by mass of total ceramic powder) of polyvinyl alcohol (PVA) binder are added. The mixture is then placed in a planetary ball mill and milled at 300-400 r / min for 12-24 h to obtain a uniform ceramic slurry. The ceramic slurry is then spray-granulated to obtain ceramic powder with a particle size of 80-120 μm. The spray granulation process parameters are: inlet air temperature 220-250 ℃, outlet air temperature 100-120 ℃, and atomization pressure 0.2-0.3 MPa. The ceramic powder is filled into a steel mold with a dovetail groove structure and pre-formed under dry pressing at 20-30 MPa. The pre-formed blank is sealed in a rubber sleeve and cold isostatic pressing is used, holding the pressure at 100-150 MPa for 5-10 seconds. The ceramic green body is obtained by heating for 1 minute. The green body is then removed and placed in an electric heating drying oven at 80-120 ℃ for 6-12 hours to remove moisture. The dried green body is then placed in an air-atmosphere high-temperature sintering furnace and heated to 300 ℃ at a rate of 2 ℃ / min, holding for 1 hour. The temperature is then increased to 550 ℃ at a rate of 1 ℃ / min and held for 2 hours to ensure the binder is fully decomposed and discharged. The temperature is then increased to 1550-1650 ℃ at a rate of 5-10 ℃ / min and held for sintering for 2-4 hours. The green body is then allowed to cool naturally to room temperature, resulting in a ceramic liner with a dovetail groove structure. The dovetail groove depth is 5-10 mm, the groove angle is 55°-65°, and the upper opening width is 10-15 mm. The lower opening width satisfies the following condition: lower opening width = upper opening width + 2 × groove depth × tan(angle / 2). This step, through the dovetail groove structure design, increases the mechanical engagement area between the ceramic liner and the inner wall of the equipment, providing a foundation for subsequent double fixing.

[0006] S2. Maleic anhydride modification of epoxy resin: Bisphenol A type epoxy resin, polyethylene glycol diglycidyl ether, and trimethylolpropane triglycidyl ether were added to a three-necked flask in a certain mass ratio. The flask was placed in a constant temperature water bath and heated to 60-80 ℃. The mixture was stirred at 200-300 r / min for 30-60 min to obtain a homogeneous epoxy resin mixture. Triethylamine (0.1%-0.3% by weight of the epoxy resin) was added in batches as an esterification catalyst, and maleic anhydride (5%-9% by weight) was added in batches. Nitrogen gas was purged simultaneously for protection. The mixture was heated to 80-100 ℃ and stirred at 300-400 r / min for 1-2 h to ensure complete reaction between the maleic anhydride and the epoxy resin. Stirring was performed every 30 min. Sampling was performed to determine the acid value, following GB / T2895-2008 "Determination of Partial and Total Acid Values ​​of Polyester Resins in Plastics". The reaction was stopped when the acid value reached more than 90% of the theoretical value and the change was less than 1 mg KOH / g, yielding maleic anhydride-modified epoxy resin. This step modifies the epoxy resin with maleic anhydride, introducing carboxyl polar groups into the epoxy resin molecular chain, significantly improving the polarity and adhesion of the epoxy resin, and enhancing its bonding ability to metal and ceramic surfaces.

[0007] S3. Compound Modification of Silane Coupling Agents: γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane are added to a beaker at a mass ratio of 60-70:30-40. Anhydrous ethanol, at 8-10 times the total mass of the silanes, is added. The mixture is stirred at 150-200 r / min for 10-20 min to obtain a mixed silane solution. Glacial acetic acid is added dropwise to the mixed silane solution to adjust the pH to 4-5. The mixture is then stirred at 200-300 r / min for 30-60 min to ensure complete hydrolysis of the silane coupling agent, yielding a modified silane coupling agent. The modified silane coupling agent should be used within 2 hours of preparation. Storage under sealed, light-protected conditions below 25 °C can extend this time to 4 hours to prevent self-polymerization failure. In this step, the amino terminus of γ-aminopropyltriethoxysilane condenses with the hydroxyl groups on the ceramic surface, while the amino terminus can undergo ring-opening addition with the carboxyl and epoxy groups of the modified epoxy resin. γ-glycidoxypropyltrimethoxysilane anchors the ceramic surface through silanol bonds, and its epoxy functional groups can react with the active hydrogen of the polyamide curing agent. At the same time, aminosilane and epoxysilane can undergo moderate prepolymerization to form a gradient cross-linked interfacial transition layer, which significantly improves the interfacial bonding strength and aging resistance.

[0008] S4. Plasma pretreatment of ceramic liner surface: Place the ceramic liner with dovetail groove structure obtained in step S1 into anhydrous ethanol and ultrasonically clean it for 5-10 min to remove surface oil and impurities. After removal, dry it with nitrogen. Place the cleaned ceramic liner into the reaction chamber of the plasma treatment instrument, evacuate to 10-20 Pa, introduce argon gas at a flow rate of 50-100 sccm, adjust the power to 200-300 W, and perform plasma treatment on the back of the ceramic liner and the inner wall of the dovetail groove for 3-5 min. After treatment, immediately remove the ceramic liner. Since the surface active groups generated by plasma activation will decay rapidly in air, the coating of modified silane coupling agent must be completed within 30 min. If stored under vacuum or argon protection, the coating time can be extended to 2 h. If the silane coupling agent is not coated after more than 30 min of plasma activation, plasma activation treatment needs to be repeated (treatment time shortened to 2 min). The modified silane coupling agent obtained in step S3 was uniformly coated on the back side of the ceramic liner and the inner wall of the dovetail groove, controlling the dry film thickness to be 0.5-3 μm (after wet film coating, a thin and uniform interface layer is formed by solvent evaporation), and then air-dried at room temperature for 10-20 min. This step, through plasma treatment, introduces a large number of active hydroxyl and carboxyl groups onto the surface of the ceramic liner, while also increasing the surface roughness, significantly improving the adhesion of the modified silane coupling agent to the ceramic surface.

[0009] S5. Assembly and application of dovetail groove double-fixed ceramic liner: Mix the maleic anhydride modified epoxy resin obtained in step S2 with the polyamide curing agent at a mass ratio, and stir at a speed of 200-300 r / min for 10-15 min to obtain the adhesive. The adhesive should be used within 30 min at 25℃. The pot life is shortened by about 50% for every 10℃ increase in temperature to avoid premature gelation and curing. The pot life of the adhesive is determined by measuring the rotational viscosity at 25℃ using a Brookfield viscometer (rotor No. 2, 6 r / min). Use should be stopped when the viscosity reaches 5000 mPa·s. Apply adhesive evenly to the surface of the pre-welded Q235 carbon steel dovetail boss on the inner wall of the equipment (the boss surface needs to be sandblasted to remove rust, with a roughness Ra≥12.5 μm; sandblasting process parameters: use brown corundum abrasive (particle size 80-100 mesh), sandblasting pressure 0.4-0.6 MPa, sandblasting distance 100-150 mm), as well as the back of the ceramic liner and the inner wall of the dovetail groove. The upper opening width of the dovetail groove is 12 mm, the lower opening width is 20 mm, and the coating thickness is controlled at 0.3-0.6 mm. Align the dovetail groove of the liner with the dovetail boss of the equipment, push it in along the groove opening direction, and adjust the pressure direction to be parallel to the bottom of the groove. Apply a uniform pressure of 0.1-0.3 MPa, and control the pushing speed at 5-10 mm / s. Do not strike violently to avoid cracking the ceramic liner. The pressure distribution deviation should not exceed ±10%, and the pressure should be kept constant. Place the entire equipment in an electric heating forced-air drying oven at 60-80°C. The ceramic liner is cured at ℃ for 2-4 hours and then naturally cooled to room temperature to obtain a dovetail groove double-fixed ceramic liner. This step combines the chemical bonding of the modified epoxy resin adhesive with the mechanical interlocking of the dovetail groove to achieve double fixation of the ceramic liner, significantly improving the fixation firmness.

[0010] Preferably, in step S1, the mass ratio of alumina ceramic powder, silica powder, and magnesium oxide powder is 90:5:5; the amount of deionized water added is 35% of the total mass of ceramic powder (example: 350 g of deionized water, density ≈ 1 g / mL at 25 ℃); the amount of sodium polyacrylate dispersant added is 1% of the total mass of ceramic powder; the ball milling speed is 350 r / min; the ball milling time is 18 h; the isostatic pressing pressure is 120 MPa; the holding time is 8 min; the drying temperature is 100 ℃; the drying time is 9 h; the sintering heating rate is 7 ℃ / min; the sintering temperature is 1600 ℃; and the sintering time is 3 h.

[0011] Preferably, in step S2, the mass ratio of bisphenol A epoxy resin, polyethylene glycol diglycidyl ether, and trimethylolpropane triglycidyl ether is 75:12:13, the heating temperature is 70 °C, the stirring time is 45 min, the amount of maleic anhydride added is 7% of the mass of the mixed epoxy resin, the heating temperature is continued at 90 °C, and the stirring time is 1.5 h.

[0012] Preferably, in step S3, the mass ratio of γ-aminopropyltriethoxysilane to γ-glycidoxypropyltrimethoxysilane is 65:35, the amount of anhydrous ethanol added is 8-10 times the total mass of the mixed silanes, the amount of glacial acetic acid added is 0.7% of the mass of the mixed silane solution (Example: 7.4 g glacial acetic acid, density ≈ 1.05 g / mL at 25°C), the pH is adjusted to 4.5, and the stirring time is 45 min.

[0013] Preferably, in step S4, the ultrasonic cleaning time of anhydrous ethanol is 8 min, the power of the plasma treatment instrument is 250 W, the gas pressure is 15 Pa, the treatment time is 4 min, the dry film thickness of the modified silane coupling agent is 1-3 μm, and the drying time is 15 min.

[0014] Preferably, in step S5, the mass ratio of maleic anhydride modified epoxy resin to polyamide curing agent is 2.5:1, the stirring time is 12 min, the coating thickness of the adhesive is 0.4 mm, the applied pressure is 0.2 MPa, the curing temperature is 70 ℃, and the curing time is 3 h.

[0015] Preferably, in step S1, the dovetail groove of the ceramic liner has a depth of 7 mm, an angle of 60°, an upper opening width of 12 mm, a lower opening width of 20 mm, and a spacing of 75 mm between adjacent dovetail grooves.

[0016] Preferably, in step S5, the dovetail boss pre-welded to the inner wall of the equipment has a height of 6.5 mm, an angle of 60°, and a single-sided gap of 0.12 mm with the dovetail groove.

[0017] Advantages of this invention 1. This invention significantly improves the bonding strength between the ceramic liner and the inner wall of the equipment by combining the mechanical interlocking of the dovetail groove with the chemical bonding of the modified adhesive, effectively avoiding the problem of the ceramic liner falling off under strong impact and high wear conditions.

[0018] 2. This invention uses maleic anhydride to modify epoxy resin, introducing polar carboxyl groups. At the same time, through the compound modification of two silane coupling agents, a dual chemical reaction is achieved between the silane coupling agent and the ceramic surface and the modified epoxy resin. The synergistic effect of the two significantly improves the interfacial adhesion performance.

[0019] 3. This invention introduces plasma surface pretreatment technology, which increases the surface roughness and the number of active groups without damaging the ceramic liner structure, further enhancing the adhesion of the modified silane coupling agent and improving the overall bonding effect.

[0020] 4. The preparation process of this invention is simple and controllable, easy to operate, and the raw materials used are all commonly used industrial products that meet relevant national safety production and environmental protection standards. The cost is low and it is suitable for large-scale industrial production and application.

[0021] 5. The dovetail groove double-fixed ceramic liner prepared by the present invention maintains the excellent wear resistance of alumina ceramic itself, while significantly improving the bonding strength, impact resistance and corrosion resistance. It can adapt to various harsh working conditions, significantly extend the service life of the equipment, and reduce maintenance costs and downtime. Attached Figure Description

[0022] Figure 1 A bar chart comparing the bonding strength of each group of samples at room temperature; Figure 2 A bar chart comparing the critical impact counts of each group of samples; Figure 3 This is a physical sample image of the wear-resistant liner plate of the present invention. Detailed Implementation

[0023] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features described therein can be combined with each other.

[0024] The sources and specifications of the raw materials used in the embodiments of this application are as follows: All reagents used in the laboratory research phase of this invention are of analytical grade, while industrial-grade raw materials that meet relevant national standards are used in industrial production.

[0025] Bisphenol A type epoxy resin was purchased from Jiangsu Sanmu Group Co., Ltd. Polyethylene glycol diglycidyl ether was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd. Trimethylolpropane triglycidyl ether and maleic anhydride were both purchased from Sinopharm Chemical Reagent Co., Ltd. γ-aminopropyltriethoxysilane was purchased from Guangzhou Weber Technology Co., Ltd. γ-glycidyl etheroxypropyltrimethoxysilane was purchased from Hubei Jianghan New Materials Co., Ltd. The polyamide curing agent was purchased from Shandong Jiayu Chemical Co., Ltd. In this invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in this industry.

[0026] Example 1

[0027] S1. Forming of the dovetail groove structure of the ceramic liner: Weigh 900 g of alumina ceramic powder, 50 g of silica powder, and 50 g of magnesium oxide powder, and mix them to obtain a total mass of 1000 g of ceramic mixed powder; add 350 mL of deionized water, 10 g of sodium polyacrylate dispersant, and 12 g of polyvinyl alcohol (PVA) binder (accounting for 1.2% of the total mass of ceramic powder) to the powder, and put all materials into a planetary ball mill. Set the ball mill speed to 350 r / min and continuously ball mill for 18 h to obtain a uniform ceramic slurry. Ceramic powder was filled into a steel mold with a dovetail groove structure and pre-formed by dry pressing at 25 MPa. The pre-formed green body was then sealed in a rubber sleeve and pressed at 120 MPa for 8 minutes using an isostatic press to obtain a ceramic green body. The green body was placed in an electrically heated forced-air drying oven and dried at 100 ℃ for 9 hours. After drying, the green body was transferred to a high-temperature sintering furnace and heated to 1600 ℃ at a rate of 7 ℃ / min, and sintered at that temperature for 3 hours. It was then allowed to cool naturally to room temperature in the furnace to obtain a ceramic liner with dovetail grooves. This step completes the forming of the liner substrate and the mechanical fixing structure. The dovetail groove depth is 7 mm, the groove angle is 60°, and the distance between adjacent grooves is 75 mm.

[0028] S2. Maleic anhydride modification of epoxy resin: 750 g of bisphenol A type epoxy resin, 120 g of polyethylene glycol diglycidyl ether, and 130 g of trimethylolpropane triglycidyl ether were added sequentially to a three-necked flask. The flask was placed in a constant temperature water bath at 70 ℃, and the stirring speed was 250 r / min for 45 min to obtain a mixed epoxy resin system. 2 g of triethylamine was added to the above mixed system as a catalyst, and 70 g of maleic anhydride was added in batches. The water bath temperature was increased to 90 ℃, the stirring speed was adjusted to 350 r / min, and stirring was continued for 1.5 h to complete the grafting modification, thus obtaining maleic anhydride-modified epoxy resin. This step improves the adhesive activity of the resin through functional group modification.

[0029] S3. Modification of Silane Coupling Agents: Weigh 65 g of γ-aminopropyltriethoxysilane and 35 g of γ-glycidoxypropyltrimethoxysilane into a beaker, add 850 g of anhydrous ethanol, and stir at 180 r / min for 15 min to obtain a mixed silane solution. Slowly add 7 mL of glacial acetic acid to the solution to adjust the pH to 4.5, adjust the stirring speed to 250 r / min, and continue stirring for 45 min to ensure complete hydrolysis of the silane coupling agents, thus obtaining the modified silane coupling agent. This step achieves synergistic modification of the two silane coupling agents, strengthening the interfacial bonding force.

[0030] S4. Plasma Pretreatment of Ceramic Liner Surface: Take the ceramic liner prepared in S1, place it in a CNC ultrasonic cleaner, immerse the sample in anhydrous ethanol, and ultrasonically clean for 8 minutes to remove surface impurities and dust. After removal, purge with nitrogen gas at room temperature until the surface is completely dry. Place the dried ceramic liner into the reaction chamber of the plasma treatment instrument, evacuate to 15 Pa, continuously introduce argon gas, set the equipment power to 250 W, and treat the back of the liner and the inner wall of the dovetail groove for 4 minutes. Immediately after treatment, remove it and uniformly coat the treated surface with the modified silane coupling agent prepared in S3, controlling the dry film thickness to about 2 μm, and allow it to air dry at room temperature for 15 minutes. This step utilizes plasma to activate the ceramic surface, further improving the coating adhesion.

[0031] Assembly and Application of S5 Dovetail Groove Double-Fixing Ceramic Liner: Mix 250 g of modified epoxy resin obtained from S2 and 100 g of polyamide curing agent at a stirring speed of 250 r / min for 12 min to prepare the adhesive. Apply the adhesive evenly to the surface of the pre-machined dovetail boss (6.5 mm height, 60° angle) on the inner wall of the equipment, the back of the ceramic liner, and the inner wall of the dovetail groove, with a coating thickness of 0.4 mm. Align the dovetail groove of the liner with the dovetail boss of the equipment, push it in along the groove opening direction, and adjust the pressure direction to be parallel to the bottom of the groove. Apply a uniform pressure of 0.2 MPa and maintain it constant. Transfer the assembled workpiece into an electric heating drying oven, set the temperature to 70 ℃, and cure at a constant temperature for 3 h. Allow it to cool naturally to room temperature to obtain the finished dovetail groove double-fixing ceramic liner. This step combines mechanical interlocking and chemical bonding to achieve double fixation.

[0032] Example 2

[0033] S1. Forming of the dovetail groove structure of the ceramic liner: The raw material ratio and preparation process are the same as in Example 1, except that 12 g of polyvinyl alcohol (PVA) binder (accounting for 1.2% of the total mass of ceramic powder) is added, the ball milling speed is 300 r / min, the ball milling time is 12 h, the isostatic pressing pressure is 100 MPa, the holding time is 5 min, the drying temperature is 80 ℃, the drying time is 6 h, the sintering temperature is 1550 ℃, and the sintering time is 2 h; the resulting ceramic liner dovetail groove has a depth of 7 mm, a groove angle of 60°, and a spacing of 75 mm between adjacent grooves.

[0034] S2. Maleic anhydride modification of epoxy resin: 750 g of bisphenol A epoxy resin, 120 g of polyethylene glycol diglycidyl ether, and 130 g of trimethylolpropane triglycidyl ether were added sequentially to a three-necked flask. The flask was placed in a constant-temperature water bath at 60 ℃, and the stirring speed was 200 r / min for 30 min to obtain a mixed epoxy resin system. 2 g of triethylamine was added to the mixture as a catalyst, and 60 g of maleic anhydride was added in batches. The water bath temperature was increased to 80 ℃, the stirring speed was adjusted to 300 r / min, and stirring was continued for 1 h to complete the grafting modification, thus obtaining maleic anhydride-modified epoxy resin. This step improves the adhesive activity of the resin through functional group modification.

[0035] S3. Modification of Silane Coupling Agents: Weigh 65 g of γ-aminopropyltriethoxysilane and 35 g of γ-glycidoxypropyltrimethoxysilane into a beaker, add 850 g of anhydrous ethanol, and stir at 150 r / min for 10 min to obtain a mixed silane solution. Slowly add 6 mL of glacial acetic acid to the solution to adjust the pH to 4.0, adjust the stirring speed to 200 r / min, and continue stirring for 30 min to fully hydrolyze the silane coupling agents, thus obtaining the modified silane coupling agent. This step achieves synergistic modification of the two silane coupling agents, strengthening the interfacial bonding force.

[0036] S4. Plasma Pretreatment of Ceramic Liner Surface: Take the ceramic liner prepared in S1, place it in a CNC ultrasonic cleaner, immerse the sample in anhydrous ethanol, and ultrasonically clean for 5 min to remove surface impurities and dust; after removal, purge with nitrogen at room temperature until the surface is completely dry. Place the dried ceramic liner into the reaction chamber of the plasma treatment instrument, evacuate to 10 Pa, continuously introduce argon gas, set the equipment power to 200 W, and treat the back of the liner and the inner wall of the dovetail groove for 3 min. Immediately after treatment, remove it and uniformly coat the treated surface with the modified silane coupling agent prepared in S3, controlling the dry film thickness to about 1 μm, and allow it to air dry at room temperature for 10 min. This step utilizes plasma to activate the ceramic surface, further improving the coating adhesion.

[0037] Assembly and Application of S5 Dovetail Groove Double-Fixing Ceramic Liner: Mix 250 g of modified epoxy resin prepared from S2 and 100 g of polyamide curing agent at a stirring speed of 200 r / min for 10 min to prepare the adhesive. Apply the adhesive evenly to the surface of the pre-machined dovetail boss (6.5 mm height, 60° angle) on the inner wall of the equipment, the back of the ceramic liner, and the inner wall of the dovetail groove, with a coating thickness of 0.3 mm. Align the dovetail groove of the liner with the dovetail boss of the equipment, push it in along the groove opening direction, and adjust the pressure direction to be parallel to the bottom of the groove. Apply a uniform pressure of 0.1 MPa and maintain it constant. Transfer the assembled workpiece into an electric heating drying oven, set the temperature to 60 ℃, and cure at a constant temperature for 2 h. Allow it to cool naturally to room temperature to obtain the finished dovetail groove double-fixing ceramic liner. This step combines mechanical interlocking and chemical bonding to achieve double fixation.

[0038] Example 3

[0039] S1. Forming of the dovetail groove structure of the ceramic liner: The raw material ratio and preparation process are the same as in Example 1, except that 12 g of polyvinyl alcohol (PVA) binder (accounting for 1.2% of the total mass of ceramic powder) is added, the ball milling speed is 400 r / min, the ball milling time is 24 h, the isostatic pressing pressure is 150 MPa, the holding time is 10 min, the drying temperature is 120 ℃, the drying time is 12 h, the sintering temperature is 1650 ℃, and the sintering time is 4 h; the resulting ceramic liner dovetail groove has a depth of 7 mm, a groove angle of 60°, and a spacing of 75 mm between adjacent grooves.

[0040] S2. Maleic anhydride modification of epoxy resin: 750 g of bisphenol A epoxy resin, 120 g of polyethylene glycol diglycidyl ether, and 130 g of trimethylolpropane triglycidyl ether were added sequentially to a three-necked flask. The flask was placed in a constant-temperature water bath at 80 ℃, and the stirring speed was 300 r / min for 60 min to obtain a mixed epoxy resin system. 2 g of triethylamine was added to the mixture as a catalyst, followed by 80 g of maleic anhydride in batches. The water bath temperature was increased to 100 ℃, and the stirring speed was adjusted to 400 r / min. Stirring was continued for 2 h to complete the grafting modification, yielding maleic anhydride-modified epoxy resin. This step improves the adhesive activity of the resin through functional group modification.

[0041] S3. Modification of Silane Coupling Agents: Weigh 65 g of γ-aminopropyltriethoxysilane and 35 g of γ-glycidoxypropyltrimethoxysilane into a beaker, add 850 g of anhydrous ethanol, and stir at 200 r / min for 20 min to obtain a mixed silane solution. Slowly add 8 mL of glacial acetic acid to the solution to adjust the pH to 5.0, adjust the stirring speed to 300 r / min, and continue stirring for 60 min to ensure complete hydrolysis of the silane coupling agents, thus obtaining the modified silane coupling agent. This step achieves synergistic modification of the two silane coupling agents, strengthening the interfacial bonding force.

[0042] S4. Plasma Pretreatment of Ceramic Liner Surface: Take the ceramic liner prepared in S1, place it in a CNC ultrasonic cleaner, immerse the sample in anhydrous ethanol, and ultrasonically clean for 10 min to remove surface impurities and dust; after removal, purge with nitrogen at room temperature until the surface is completely dry. Place the dried ceramic liner into the reaction chamber of the plasma treatment instrument, evacuate to 20 Pa, continuously introduce argon gas, set the equipment power to 300 W, and treat the back of the liner and the inner wall of the dovetail groove for 5 min. Immediately after treatment, remove it and uniformly coat the treated surface with the modified silane coupling agent prepared in S3, controlling the dry film thickness to about 3 μm, and allow it to air dry at room temperature for 20 min. This step utilizes plasma to activate the ceramic surface, further improving the coating adhesion.

[0043] Assembly and Application of S5 Dovetail Groove Double-Fixing Ceramic Liner: Mix 250 g of modified epoxy resin prepared from S2 and 100 g of polyamide curing agent at a stirring speed of 300 r / min for 15 min to prepare the adhesive. Apply the adhesive evenly to the surface of the pre-machined dovetail boss (6.5 mm high, 60° angle) on the inner wall of the equipment, the back of the ceramic liner, and the inner wall of the dovetail groove, with a coating thickness of 0.6 mm. Align the dovetail groove of the liner with the dovetail boss of the equipment, push it in along the groove opening direction, and adjust the pressure direction to be parallel to the bottom of the groove. Apply a uniform pressure of 0.3 MPa and maintain it constant. Transfer the assembled workpiece into an electric heating drying oven, set the temperature to 80 ℃, and cure at a constant temperature for 4 h. Allow it to cool naturally to room temperature to obtain the finished dovetail groove double-fixing ceramic liner. This step combines mechanical interlocking and chemical bonding to achieve double fixation.

[0044] Comparative Example 1: In step S2, maleic anhydride was not added for graft modification. Instead, a mixed epoxy resin system consisting of 750 g of bisphenol A epoxy resin, 120 g of polyethylene glycol diglycidyl ether, and 130 g of trimethylolpropane triglycidyl ether was used directly. All other steps were the same as in Example 1.

[0045] Comparative Example 2: In step S3, only 65 g of γ-aminopropyltriethoxysilane was used, without adding 35 g of γ-glycidoxypropyltrimethoxysilane, and the remaining hydrolysis modification steps were the same as in Example 1; all other steps were the same as in Example 1.

[0046] Comparative Example 3: In step S4, no plasma activation treatment was performed. The ceramic liner was only ultrasonically cleaned with anhydrous ethanol for 8 minutes and dried with nitrogen at room temperature before being directly coated with a modified silane coupling agent. All other steps were the same as in Example 1.

[0047] Comparative Example 4: No modified epoxy resin or modified silane coupling agent was prepared, and no plasma pretreatment was performed; ordinary bisphenol A type epoxy resin (the same grade used in Example 1) was used as the adhesive; the ceramic liner had no dovetail groove structure and was directly pasted onto the surface of the carbon steel substrate; all other steps were the same as in Example 1.

[0048] Comparative Example 5: Without applying any modified silane coupling agent or adhesive, the ceramic liner with dovetail grooves prepared in Example 1 was directly assembled to the dovetail boss on the inner wall of the equipment. After applying a uniform pressure of 0.2 MPa, it was left to stand naturally for 24 hours; no heat curing treatment was performed. All other steps were the same as in Example 1.

[0049] I. Performance Testing Experiment Eight groups of samples were selected for performance testing: Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5. Five parallel samples were set up in each group, and the average value of the test results was taken. All tests were carried out in a standard environment with a temperature of 23±2 ℃ and a relative humidity of 50±5 %.

[0050] 1. Interface bond strength test The test was performed according to GB / T 6329-1996 "Determination of Tensile Strength of Butt Joints of Adhesives". The sample size was 25 mm × 25 mm × 10 mm, and the bonding area was 25 mm × 25 mm. Testing instrument: Electronic universal tensile testing machine Sample preparation: Each component liner is assembled with a commonly used industrial carbon steel substrate to form a standard test sample block with uniform overall dimensions.

[0051] Test Procedure: During sample bonding, apply adhesive, assemble, pressurize, and cure according to the process parameters in step S5 to ensure consistency with the actual product process. Fix both ends of the test sample in the upper and lower clamps of the tensile testing machine to ensure that the sample is vertically aligned without deviation under force; set the tensile speed to 5 mm / min, start the equipment for continuous tensile testing, and record the maximum tensile force value when the sample detaches or delaminates; calculate the average bond strength based on the stress area.

[0052] Judgment criteria: The higher the bonding strength value, the stronger the bond between the backing and the substrate.

[0053] Table 1 Comparison of core bonding strength among samples in each group

[0054] Note: *P<0.05, statistically significant compared to Comparative Example 4; **P<0.01, highly statistically significant compared to Comparative Example 4; #P<0.05, statistically significant compared to all other comparative examples.

[0055] 2. Bond strength test after high temperature aging Testing instruments: High and low temperature aging test chamber, electronic universal tensile testing machine Sample preparation: Take finished product samples from each batch and divide them into aging test groups.

[0056] Test procedure: Place the sample in a high and low temperature aging test chamber, set the temperature to 120℃, and keep it at a constant temperature for 200 h. After aging, take out the sample, let it cool naturally to room temperature, and test the bonding strength again according to the method of Test 1 to compare the performance changes before and after aging.

[0057] Judgment criteria: The smaller the decrease in bonding strength after aging, the better the product's temperature resistance and aging resistance.

[0058] 3. Bond strength test after thermal cycling Testing instruments: High and low temperature alternating test chamber (model: GDJS-100, Shanghai Yiheng Scientific Instruments Co., Ltd.), electronic universal tensile testing machine Sample preparation: Take finished product samples from each combination and divide them into cold and hot cycle test groups.

[0059] Test procedure: Place the sample in a high and low temperature alternating test chamber, set the temperature range to -20 ℃ to 120 ℃, the heating and cooling rate to 5 ℃ / min, each cycle to 4 h (hold at -20 ℃ for 2 h, hold at 120 ℃ for 2 h), and perform 50 cycles continuously; after the cycle is completed, take out the sample, let it cool naturally to room temperature, and test the bonding strength again according to the method of Test 1, and compare the performance changes before and after the cycle.

[0060] Judgment criteria: After cycling, the sample is considered to be visually acceptable if there is no interface cracking, no loosening or falling off of the liner, and no peeling of the adhesive layer. At the same time, the adhesive strength retention rate is tested; the smaller the decrease in adhesive strength, the better the product's resistance to temperature changes.

[0061] 4. Wear resistance test GB / T 3810.6-2016 "Test Methods for Ceramic Tiles - Part 6: Determination of Resistance to Deep Abrasion for Unglazed Tiles", the specimen size is 100 mm × 25 mm × 2 mm, and the overlapping area is 25 mm × 12.5 mm Test apparatus: Ceramic abrasion tester Specimen preparation: Cut each group of ceramic lining boards into specimens of uniform specification, weigh with an electronic balance and record the initial mass of the specimens.

[0062] Test procedure: Fix the specimen on the station of the abrasion tester, select quartz sand as the abrasion medium, set the equipment rotation speed to 60 r / min, and conduct continuous abrasion test for 2 h; after the test is completed, take out the specimen, clean the dust and impurities on the surface, weigh the specimen mass again, and calculate the difference in abrasion mass.

[0063] Judgment criteria: The smaller the abrasion mass, the more excellent the wear resistance of the product. After the 2-hour abrasion test, the abrasion mass of the ceramic lining board of the present invention is significantly lower than that of Comparative Example 4, which is regarded as qualified in wear resistance.

[0064] 5. Impact resistance test The impact spalling resistance of the lining board is tested by the drop hammer impact method, which is implemented with reference to Appendix C of GB / T 23266-2009 "Ceramic Boards".

[0065] Test apparatus: Drop hammer impact tester Specimen preparation: Assemble each group of finished lining boards with a carbon steel substrate of 100 mm × 100 mm × 10 mm into test specimens, and fix them horizontally on the special base of the tester.

[0066] Test procedure: Select a 1 kg standard steel drop hammer with a drop height of 50 cm (impact energy 4.9 J), and perform a single free-fall impact on the center position of the specimen surface; accumulate the number of impacts step by step, observe the state of the specimen in real time, and record the critical number of impacts when the specimen shows cracks, local spalling, or overall loosening.

[0067] Judgment criteria: The greater the critical number of impacts, the stronger the impact resistance of the product. Under the condition of impact energy of 4.9 J, the ceramic lining board of the present invention is regarded as qualified in impact resistance when the critical number of impacts is ≥ 50 times (formulated by referring to the impact resistance requirements for ceramic boards in GB / T 23266-2009 and combining with the actual demands of industrial working conditions).

[0068] The environmental aging resistance test results are as follows: Table 2 Comparison of environmental aging resistance of each group of samples

[0069] Note: *P<0.05, statistically significant compared to Comparative Example 4; **P<0.01, highly statistically significant compared to Comparative Example 4; #P<0.05, statistically significant compared to all other comparative examples.

[0070] Table 3 Comparison of wear resistance and impact resistance of samples in each group

[0071] Note: *P<0.05, statistically significant compared to Comparative Example 4; **P<0.01, highly statistically significant compared to Comparative Example 4; #P<0.05, statistically significant compared to all other comparative examples.

[0072] Comparative Example 5 uses a purely mechanical fixation method. The bonding strength test method is as follows: the dovetail boss is fixed in the lower fixture of the tensile testing machine, the ceramic liner is fixed in the upper fixture, and the machine is stretched vertically upward at a speed of 5 mm / min. The maximum tensile force when the liner separates from the boss is recorded.

[0073] As shown in Table 1, the performance indicators of Examples 1-3 are significantly better than those of Comparative Examples 1-5, with Example 1 exhibiting the best overall performance. The room temperature bonding strength of Comparative Example 5 (mechanical fixation only for the dovetail groove) is only 0.82 MPa, and the critical impact count is only 18, far lower than the 8.62 MPa and 126 impact counts of Example 1. After high-temperature aging and thermal cycling, its bonding strength is approximately 0.78 MPa and 0.75 MPa, respectively, with a strength retention rate exceeding 90%. This indicates that Comparative Example 5 is purely mechanically fixed without adhesive participation, thus avoiding adhesive aging and failure issues. Its strength change stems solely from the minor deformation caused by thermal expansion and contraction of the metal boss, demonstrating the excellent environmental stability of mechanical fixation. However, the initial strength of purely mechanical fixation is low and cannot withstand strong impact loads.

[0074] The room temperature bond strength of Comparative Example 1 (unmodified epoxy resin) decreased by 38.4% compared to Example 1, and the decrease rate after high-temperature aging was as high as 28.1%, strongly demonstrating that maleic anhydride-modified epoxy resin is a key factor in improving bond strength and aging resistance. The room temperature bond strength of Comparative Example 2 (single silane coupling agent) decreased by 29.1% compared to Example 1, indicating that the combination of two functional group silane coupling agents can achieve a dual chemical reaction with the ceramic surface and epoxy resin, significantly enhancing the interfacial bonding force. The room temperature bond strength of Comparative Example 3 (without plasma pretreatment) decreased by 24.4% compared to Example 1, verifying that plasma treatment effectively improves the adhesion of the silane coupling agent by increasing surface active groups and roughness. Comparative Example 4 (traditional adhesive method) had the worst performance indicators, with a critical impact count of only 32, making it extremely prone to detachment under strong impact conditions, further highlighting the significant advantages of the dual fixing structure of this invention compared to the prior art. The wear mass of Comparative Example 5 after 2 hours was 0.085 g, which is basically equivalent to 0.082 g in Example 1. This indicates that the wear resistance of the ceramic liner is mainly determined by the matrix material. The improvement of this invention focuses on enhancing the bonding strength and impact resistance without affecting the wear resistance of the ceramic itself.

[0075] The above data corroborate each other, confirming that the present invention achieves a perfect combination of high stability of mechanical fixation and high strength of chemical bonding through a dual fixing system of "dovetail groove mechanical interlocking + modified adhesive chemical bonding". The synergistic effect of the two solves the problems of poor aging resistance and impact resistance of chemical bonding alone, and also makes up for the insufficient strength of mechanical fixation alone. This is the core mechanism for solving the problem of ceramic liner detachment under harsh working conditions.

[0076] Figure 3 The image shows a physical sample of the wear-resistant liner of this invention: the white substrate is an alumina ceramic wear-resistant block with a prefabricated integrated concave-convex interlocking structure; the right side shows a matching metal slot component. The ceramic block can be interlocked with the metal slot, forming a mechanical self-locking mechanism through the interlocking structure, and achieving double fixation with adhesive material.

[0077] The above-described embodiments are merely illustrative of specific implementations of the present invention, and while the descriptions are detailed, they should not be construed as limiting the scope of protection of the present invention. It should be noted that for those skilled in the art, any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the scope of protection of the present invention.

Claims

1. A manufacturing process for a dovetail groove double-fixed ceramic liner, characterized in that, Includes the following steps: S1. Alumina ceramic powder, silica powder, and magnesium oxide powder are mixed in a mass ratio of 85-95:3-7:2-6. 35% of the total mass of the ceramic powder is added to deionized water, 0.5%-1% to sodium polyacrylate dispersant, and 0.8%-1.5% to polyvinyl alcohol (PVA) binder. The mixture is ball-milled to form a slurry. The slurry is then spray-granulated to obtain ceramic powder with a particle size of 80-120 μm. The powder is then dry-pressed under 20-30 MPa pressure, cold isostatically pressed at 100-150 MPa, dried, debinded, and sintered at 1550-1650 ℃ to obtain a ceramic liner with a dovetail groove structure. S2. Maleic anhydride was used to graft and modify the epoxy resin system to obtain a modified epoxy resin. S3. Two silane coupling agents with different functional groups were combined and then hydrolyzed to obtain modified silane coupling agents. S4. The sintered ceramic liner is cleaned and plasma activated, and then the modified silane coupling agent is coated on the surface within 30 min. S5. Obtain a ceramic liner coated with a modified silane coupling agent, as well as matching modified epoxy resin components and polyamide curing agent components, for later use.

2. The preparation process of the dovetail groove double-fixed ceramic liner according to claim 1, characterized in that, In step S2, the epoxy resin system is composed of bisphenol A type epoxy resin, polyethylene glycol diglycidyl ether, and trimethylolpropane triglycidyl ether in a mass ratio of 70-80:10-15:10-15. Triethylamine is added as a catalyst at 0.1%-0.3% of the mass of the mixed epoxy resin, and maleic anhydride is added at 5%-9% of the mass of the mixed epoxy resin. The modification is completed by reacting at 80-100 °C for 1-2 h.

3. The preparation process of the dovetail groove double-fixed ceramic liner according to claim 1, characterized in that, In step S3, γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane with a mass ratio of 60-70:30-40 are compounded, and anhydrous ethanol of 8-10 times the total mass of silane is added. The pH value is adjusted to 4-5 with glacial acetic acid, and hydrolysis is carried out for 30-60 min to obtain the modified silane coupling agent.

4. The preparation process of the dovetail groove double-fixed ceramic liner according to claim 1, characterized in that, In step S4, the ceramic liner is ultrasonically cleaned with anhydrous ethanol for 5-10 min. Then, argon gas with a flow rate of 50-100 sccm is introduced at a working pressure of 10-20 Pa, and plasma activation treatment is performed on the back of the liner and the inner wall of the dovetail groove at a power of 200-300 W for 3-5 min.

5. The preparation process according to claim 1, characterized in that, The polyamide curing agent used in step S5 has an amine value of 200-300 mg KOH / g, is liquid at room temperature, and has a pot life of ≥30 min at 25℃ after being mixed with the modified epoxy resin.

6. A dovetail groove double-fixed ceramic liner, characterized in that: The substrate of the liner is alumina ceramic, and 1-2 dovetail grooves are opened on the back. The depth of the dovetail grooves is 5-10 mm, and the included angle of the grooves is 55°-65°. The width of the lower opening and the width of the upper opening satisfy the geometric relationship, wherein the width of the upper opening is 10-15 mm, and the dimensional tolerance is ± 0.1 mm. The back of the liner and the inner wall of the dovetail grooves are coated with a modified silane coupling agent layer of 0.5-3 μm thickness in sequence.

7. The dovetail groove double-fixed ceramic liner according to claim 6, characterized in that, The modified silane coupling agent layer is prepared by hydrolysis of a compound of γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a mass ratio of 60-70:30-40.

8. The dovetail groove double-fixed ceramic liner according to claim 7, characterized in that: The overall dimensions of the ceramic liner are 100 mm × 100 mm × 10-20 mm or 150 mm × 150 mm × 15-25 mm; the dimensional tolerances of the ceramic liner are: length / width ±0.2 mm, thickness ±0.1 mm; the dimensional tolerances of the dovetail groove are: angle ±0.5°, depth ±0.1 mm, and top width ±0.1 mm.

9. A method for installing and fixing a dovetail groove double-fixed ceramic liner plate prepared by the preparation process described in any one of claims 1-6, characterized in that, include: Modified epoxy resin and polyamide curing agent are compounded at a mass ratio of 2-3:1 to form an adhesive. The adhesive is then uniformly coated onto the dovetail bosses on the inner wall of the equipment, the back of the ceramic liner, and the inner wall of the dovetail groove, with a coating thickness of 0.3-0.6 mm. The dovetail groove of the liner is aligned with the dovetail boss of the equipment and pushed in along the groove opening. The pressure direction is adjusted to be parallel to the bottom of the groove, and a uniform pressure of 0.1-0.3 MPa is applied. The mixture is then cured at 60-80℃ for 2-4 hours to complete the double fixation.

Citation Information

Patent Citations

  • High-temperature-resistant and wear-resistant ceramic insert

    CN214698634U

  • Ceramic wear-resistant plate for kiln

    CN222865585U